Oferta e execução de testes rápidos para infecções sexualmente transmissíveis em Centros de Saúde da regional Nordeste de Belo Horizonte: A perspectiva dos profissionais de saúde - Shirley Monteiro Dias (2022)
According to the World Health Organization, more than one million Sexually Transmitted Infections are acquired worldwide every day, with an estimated 376 million new cases per year. Such infections are caused by numerous etiological agents transmitted, mainly through sexual contact without the use of condoms, with an infected sexual partner and, eventually, can be transmitted from mother to child or blood transfusion. As a strategy for the early diagnosis of sexually transmitted infections, the Ministry of Health provides free rapid tests in the public network, Health Centers and in Testing and Counseling Centers. The execution, reading and interpretation of the result occur in a maximum of 30 minutes, without the need for a laboratory structure, using blood samples by digital puncture or venipuncture. By objective, it was intended to describe the offer and execution of rapid tests for Sexually Transmitted Infections, from the perspective of health professionals, in Health Centers in the Northeast Region of Belo Horizonte. Methodologically, it is characterized as a case study, designed according to a qualitative approach. The study scenario took place in 15 Health Centers in the Northeast Region. Study participants were professionals recognized for their expertise in performing rapid tests indicated by the manager, totaling 15 professionals. For data collection, the interview was the instrument used, following a questionnaire with a semi-structured script. Data analysis took place through content analysis according to Bardin, which generated three thematic categories: Offer and execution of rapid tests, Service flow and Difficulties in performing rapid tests. The research followed the ethical precepts, according to Resolution 466/2012 of the National Health Council. The study showed that there are disparities in the provision and performance of rapid tests in the Health Centers of the Northeast Region of Belo Horizonte, whose critical point is related to poorly defined work processes and lack of more longitudinal and transversal permanent education. The low supply of testing in a timely manner is linked to several factors such as lack of knowledge on the part of professionals about the subgroups eligible for spontaneous testing, lack of training, low publicity to the population, inadequate infrastructure, the role of nurses in carrying out the tests and lack of interest of professionals and local managers with the theme. Therefore, it is necessary to reflect on its practice, identify its gaps, weaknesses, challenges and potentials, outlining means for its adequacy and expand the offer of such technologies in a timely manner to the population. Health education actions on sexually transmitted infections outside the community, schools, conversation circles in waiting rooms and interdisciplinarity in testing are simple attitudes that can improve the quality of access and resolution in health services.